NR STRATEGI DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN PADA UMKM DI ERA DIGITALISASI - Novien Rialdy (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2026)
Abstract The development of information technology has shifted the marketing paradigm from conventional to digital. However, many Micro, Small, and Medium Enterprises (MSMEs) are still lagging in adopting this technology. This community service aims to empower Micro, Small, and Medium Enterprises (MSMEs) in the Medan sub-district in Medan Helvetia through the implementation of digital marketing strategies. In the era of digitalization, MSME actors face significant challenges in terms of competitiveness and market reach. The methods used include observation, interviews, socialization, and direct assistance. The main work program focused on training in creating visual content using the Canva application and making digital location maps to improve consumer accessibility. The results of the activities showed an increase in the technical skills of MSME actors in marketing products online and an increased public awareness of the importance of digitalization. The main problem identified is the limitation of digital literacy and narrow market reach. Through observation, interviews, and technical assistance methods, this program implements the use of the Canva application for visual content and optimization of digital location layouts. The results show a significant improvement in the ability of MSME actors to manage product visual identity and consumer accessibility. Keywords: Digital Marketing; MSMEs; Digitization; Community Service.